Prediksi Erosi dan Sedimentasi pada Daerah Tangkapan Air Bendungan Rotiklot dengan Model Soil And Water Assessment Tool (SWAT): Prediction Of Erosion And Sedimentation In The Catchment Area Of The Rotiklot Dam Using Soil And Water Assessment Tool (Swat) - Nama, Arnoldus; Loden, Onisius; Fallo, Dedy Ardianto; Daga, Welem Malo Wunda Lero (Media Ilmiah Teknik Sipil, 2025)
The Rotiklot Dam Catchment Area is located in Belu Regency, East Nusa Tenggara Province. This research aims to forecast the rates of erosion and sedimentation utilizing the Soil and Water Assessment Tool (SWAT) method, as well as to assess the levels of erosion hazard present. According to the modeling outcomes, the average annual erosion rate within the Rotiklot Dam Catchment Area is calculated to be 18.5 tons/ha/year. The erosion hazard assessment indicates that the land within the Rotiklot Catchment Area is classified into two categories of erosion hazard levels: moderate and severe. Specifically, the area classified as having a moderate erosion hazard level encompasses 549.55 hectares, while the area categorized as having a severe erosion hazard level covers 587.55 hectares. The modeling results indicate that the average annual sediment discharge at the outlet of the catchment area leading to the dam is 1,865.75 tons per year. Over the course of the 28-year simulation period, the cumulative sediment total amounts to 106,317.1 tons.